Progress of cGVHD pathogenesis from the perspective of B cells - Xiaoping Li; Xi Zhang (Blood Science, 2019)
Abstract. An increasing number of physicians realize that chronic graft-versus-host disease (cGVHD) is not just dominated by T cells and that B cells also play a vital role in cGVHD development. It has been reported that altered B cell subsets, aberrant B cell signaling pathways, antibody deposition, and abnormal T-B interactions can be observed in many cGVHD patients. Studies of B cells in cGVHD development are now mainly focused on B cell subsets and GC destruction. These two aspects describe the process of B cell evolution in cGVHD patients and are associated with some original treatments. In this review, we summarize recent literature and discuss mechanisms and novel ideas of therapeutic strategies regarding the two aspects mentioned above.